Multiferroic and optical properties of Pr‐substituted bismuth ferrite ceramics. Issue 7 (15th April 2013) - Singh, Vikash; Sharma, Subhash; Dwivedi, R. K.; Kumar, Manoj; Kotnala, R. K.
<x xml:space="preserve">Abstract</x> Pr‐doped BiFeO3 ceramics with x ≤ 0.20 were synthesized by a solid‐state reaction method. X‐ray diffraction patterns of these samples have shown single‐phase rhombohedral structure with R3c space group symmetry. Remanent magnetization has been found to increase with Pr concentration. Magnetization versus temperature plots for x = 0.0 and 0.20 exhibit a broad magnetic anomaly at around 375 and 393 °C, respectively, indicating the Neel temperature "TN". Dielectric constant (ϵr) versus T plots exhibit dielectric anomalies at around 375 °C in these materials, which may correspond to the transition temperature TN. The photoluminescence spectra of these ceramics exhibit band‐edge emission in the blue region and defect‐related emission in the green region. The FTIR spectra show two broad vibrational modes at 430 and 560 cm−1.